Synthesis of 5-aryl-5´-formyl-2,2´-bithiophenes as new precursors for nonlinear optical (NLO) materials - Herbivo, Cyril (2009)
A series of formyl-substituted 5-aryl-2,2´-bithiophenes 5 were synthesized using two different methods: Vilsmeier-Haack-Arnold reaction (VHA) or through Suzuki coupling. The synthesis of compounds 5 through the Vilsmeier-Haack-Arnold reaction, starting from inexpensive and easily available precursors such as acetophenones, gave the title compounds in low yields after four reaction steps. On the other hand Suzuki coupling of functionalized aryl boronic acids 7 and the 5-bromo-5´-formyl-2,2´-bithiophene 6 gave compounds 5 in good yields in only one step.